Potensi Kawasan Grembengan Menjadi Destinasi Wisata Edukasi di Desa Bongan, Tabanan, Bali - Nelsye Lumanauw (Magister Tourism Study, Faculty of Tourism, Udayana University, 2022)
Grembengan area is a potential destination for educational tourism. Lack of awareness, understanding and knowledge of community about tourist villages have given an impact on level of community awareness. Stakeholder of the area is prefer to focus on how to bring tourists rather than solving the problems. The purpose of this research is to identify potential of Grembengan with the concept of Attraction, Accessibility, Amenity, Package, Activities, Ancillary in Bongan Village and what obstacles are faced in developing the area to become educational tourism. Qualitative research method through Focus Group Discussion. The conclusion of this study is that Grembengan has potential to become educational tourism, by fulfilling the identification of tourism components 6A. Two major problems are lack of community involvement and waste management. Community involvement is needed in the form of community empowerment as a solution to problems, as well as to maximize efforts to develop educational tourism destination. Keywords: Tourism Destinations, Educational Tourism, Tourism Village, Tourism Components.